Benign carotenaemia in children. Issue 4 (April 1981) - Congdon, P J; Kelleher, J; Edwards, P; Littlewood, J M
Abstract : Six children presented with yellow pigmentation of the skin as a result of carotenaemia, and 5 were aged less than 1 year when this was first noted. Serum carotene levels depend on carotene intake, and absorption is promoted if food is of a fine texture. Five of the children were fed a partly homogenised diet. Pigmentation resolved when the carotene intake was reduced. This condition should be suspected, especially in young children, if the skin is yellow while the sclera remains a normal colour.